Combined metabolomics and 16S rDNA sequence analyses of the gut microbiome reveal the action mechanism of Fructus Akebiae against hepatic fibrosis - Rong-Rong Wu; Duo-Rui Nie; Fang-Hui He; Zhi-Hang Li; Fei Xu; Fei Xu; Fei Xu (Frontiers in Medicine)
ObjectivesTo explore the mechanism underlying the effect of Fructus Akebiae (FAE) against hepatic fibrosis in mice through combined network pharmacology, liver metabolomics, and 16S rDNA analyses of the gut microbiota.MethodsIn this study, we randomly divided mice into the control, model, FAE high-dose, FAE medium-dose, and FAE low-dose groups to analyze the pathological changes in the hepatic fibrosis and levels of the α-SMA, collagen 1, Nuclear Factor Kappa B (NF-κ B), Toll Like Receptor 4 (TLR4). The gut microbiota was analyzed through 16S rDNA sequencing analysis of liver metabolites using liquid chromatography-mass spectrometry. Furthermore, network pharmacology was used to determine the specific molecular regulation mechanism of FAE in hepatic fibrosis treatment.ResultsFAE treatment markedly improved the pathological changes in the hepatic fibrosis. Analysis revealed that FAE administration reversed the carbon tetrachloride (CCl4)-induced dysbiosis by increasing the abundance of Akkermansia and reducing that of Cyanobacteria. Additionally, metabolomic analysis showed that FAE treatment reversed the CCl4-induced metabolic disorders by regulating amino and nucleotide sugar metabolism. Furthermore, correlation analysis showed that Akkermansia and Verrucomicobiota were closely related to D-tolasaccharide and maltotetraose saccharide. Moreover, network pharmacology indicated that FAE might regulate the signaling pathway through the JUN/CASP3/NOS3/PTGS2/HSP90AA1 during treatment.ConclusionFAE may be a promising treatment for hepatic fibrosis, and its protective effects are associated with improvements in the microbiome and metabolic disorders.